How Bank Capital Structure Affects Business Performance---- Empirical evidence from Chinese Commercial banks - Luo, Ting (2010)
In the end of 2006, China realizes the opening of financial market, thus Chinese commercial banks have to face the global competitors. How to exist and develop in the market with fierce competition has been more and more significant to Chinese commercial banks. Because commercial banks’ business performance is the overall reflection of banks’ competence, so they should consider improving the bank business performance. Thus this study aims to discuss how commercial banks’ capital structure affects its business performance, and gives the recommendations to optimize the banks’ capital structure and improve commercial banks’ business performance.